A LEGAL POLITICS IN THE FORMATION OF LAWS POST THE ENFORCEMENT CONCERNING THE FORMATION OF LEGAL REGULATIONS - Eldika Trinanda Torong; Ismaidar Ismaidar (Sean Institute, 2023)
Legislative regulations are the main way of creating law, legislative regulations are the main pillar of the national legal system in Indonesia. Besides that, Legislation is a very effective instrument in legal reform because of its binding and coercive legal power. Legal politics has a very important role in the formation of Indonesian national laws and regulations, considering that legal politics is used as a basic guideline in the process of determining values, determining, forming and developing national law in Indonesia. Therefore, through explanatory research By using a Normative and Conceptual approach, the author tries to remind again that makers of laws and regulations should remain firm in the state's goals to be achieved in making a legal product. So that the sense of justice, benefit and legal certainty for society is always accommodated in every law that is created.